2018
DOI: 10.1038/s41598-018-32734-2
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin, the major component of traditional Chinese medicine Scutellaria baicalensis induces colon cancer cell apoptosis through inhibition of oncomiRNAs

Abstract: Colorectal cancer (CRC) is among the most frequently occurring cancers worldwide. Baicalin is isolated from the roots of Scutellaria baicalensis and is its dominant flavonoid. Anticancer activity of baicalin has been evaluated in different types of cancers, especially in CRC. However, the molecular mechanisms underlying the contribution of baicalin to the treatment of CRC are still unknown. Here, we confirmed that baicalin can effectively induce and enhance apoptosis in HT-29 cells in a dose-dependent manner a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 75 publications
3
63
0
Order By: Relevance
“…In addition to the above chemical compositions, there are some other ingredients that have been isolated and identified from Scutellaria baicalensis including b-sitosterol (64), [29] benzoic acid (65) [30] and benzyl alcohol (66). [31] Furthermore, Tuan et al (2014) found that the main carotenoids in Scutellaria baicalensis were lutein (67) and b-carotene (68), and the leaves contained a lot of carotene.…”
Section: Other Chemical Componentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the above chemical compositions, there are some other ingredients that have been isolated and identified from Scutellaria baicalensis including b-sitosterol (64), [29] benzoic acid (65) [30] and benzyl alcohol (66). [31] Furthermore, Tuan et al (2014) found that the main carotenoids in Scutellaria baicalensis were lutein (67) and b-carotene (68), and the leaves contained a lot of carotene.…”
Section: Other Chemical Componentsmentioning
confidence: 99%
“…[64] In addition to these, Lin et al (2013) revealed that the EESB and its active flavonoids could reversibly inhibit myeloma SP cells, and they also discovered a potential new molecular mechanism possibly associated with the target SP cells by modulating the expression of the ABCG2 protein. [65] Recently, Tao et al [66] indicated that baicalin, the main component of Chinese medicine Scutellaria baicalensis, could significantly induce and enhance apoptosis of HT-29 colon cancer cells in a dose-and time-dependent manner, and strongly inhibit tumour growth in xenograft nude mice. [66] Their study confirmed that baicalin induced apoptosis in colon cancer cells through a mechanism possibly associated with the inhibition of c-Myc expression and downregulation of oncomiRs associated with many apoptoses.…”
Section: Antitumour Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptotic cell death is induced by baicalin treatments, and further evidence showed that various oncogenic miRNAs, such as miR-23 and miR-217, can be depleted by baicalin in colorectal cancer [ 36 , 99 ] ( Figure 2 and Table 3 ). Baicalin impedes the growth of colorectal cancer in vivo via repressing c-Myc expression in conjunction with a reduction of miR-23, which is one of the c-Myc-regulated miRNAs [ 36 ]. Additionally, baicalin can induce apoptosis through subduing Wnt/β-catenin signaling, accompanied by the upregulated levels of Dickkopf-related protein 1 (DKK1), an endogenous inhibitor of Wnt signaling [ 99 ].…”
Section: Oncogenic Mirnas Inhibited By Phytochemicals Currently Evmentioning
confidence: 99%